Encryption and Authentication in On-Board Processing Satellite Communication Systems - Ingemarsson, I.; Wong, C. (IEEE transactions on communications, 1981)
Encryption is an efficient method for information protection in communication links which are subject to wiretapping. In this paper we discuss the application of encryption to satellite communication systems in which the satellite has on-board processing capability. The on-board processor can be used in the key distribution process. Two examples of such processes are described. The first requires the storage in the satellite of one key for each user of the communication system. These are used together with a conventional encryption algorithm (DES, for example) to distribute communication keys to the users. The communication keys are then used to encrypt and decrypt information. The other key distribution process utilizes a trap-door one-way function, whose inverse is implemented in the satellite. The need for storage space in the satellite is smaller than that with the first method.